Pixel Array Application of High Temperature Superconducting Ybco Transition Edge Infrared Bolometers - Pekerten, Barış; Abukay, Doğan (Izmir Institute of Technology, 2009)
In this thesis, we patterned pregrown epitaxial YBCO thin films on MgO, LAO and STO substrates into meander shaped high-Tc superconducting transition edge monolithic bolometers. We set up and automatized the electrical characterization processes of the bolometers. We also measured the bolometric response of the meanders to red and nearinfrared light and fit them to theoretical models in literature. We compared the single pixel bolometric responses to literature and found that our results are similar to or better than the results for similar devices in the literature.We also patterned staring arrays (focal plane arrays) and explored the resolution limit put in place by thermal crosstalk. We compared the measured crosstalk to theory and found a very good agreement. We quantified the crosstalk for our pixels. We then explored substrate etching method to decrease crosstalk via thermal isolation.
Thesis (Master)--Izmir Institute of Technology, Physics, Izmir, 2009
Includes bibliographical references (leaves: 100-107)
Text in English; Abstract: Turkish and English
xvi, 107 leaves
Keywords: QC611.98.H54 .P37 2009; High temperature superconductivity; Thin films; Bolometer; Infrared imaging; Infrared dedectors